EKSISTENSI “THE TRIPS SAFEGUARDS” DI DALAM PERJANJIAN TRIPS: DALAM PERSPEKTIF KESEHATAN MASYARAKAT - Tomi Suryo Utomo (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
Developing countries believe that the TRIPS Agreement gives more benefits to pharmaceutical companies of developed countries and prevents access to cheaper and affordable drugs. A reduction of drug prices has occurred when developing countries applied safeguards, such as parallel imports and compulsory license. The effort to enact safeguard legislation has resulted in US legal action, such as the dispute between the US government and the Brazilian government when Brazil considered the adoption of compulsory license. Another example was a dispute between big pharmaceutical companies and the South African government in its plans for adoption of parallel imports and compulsory license. These disputes demonstrate that the TRIPS safeguard articles are weak and meaningless because the interpretation of those articles has favored the developed countries’ perspectives.